2005
DOI: 10.1038/sj.ejcn.1602090
|View full text |Cite|
|
Sign up to set email alerts
|

What is the best measure of adiposity change in growing children: BMI, BMI %, BMI z-score or BMI centile?

Abstract: Background: Weight control programs for obese children monitor change in body mass index (BMI) adjusted for age. However, change can be measured in several ways: raw (kg/m 2 ) units, percentage, z-scores or centiles. The suitability of the different measures is not known. Aim: To identify the optimal BMI measure for change, whose short-term variability is most consistent for children across the spectrum of adiposity. Setting: An Italian kindergarten. Subjects: A total of 135 (66 female) children aged 29-68 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
505
5
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 601 publications
(526 citation statements)
references
References 9 publications
(9 reference statements)
6
505
5
5
Order By: Relevance
“…However, if a continuous measure of relative weight is required, such as to assess change in adiposity, BMI z-scores and BMI-for-age percentiles will not be equivalent, and BMI-for-age percentiles are poorly suited for statistical analysis. 17 Analyses using BMI z-scores can be reported in BMI percentile units for interpretability, but BMI percentile should not be the analytic variable. BMI z-scores can be appropriately used to compare between group means and to model relative weight trajectories longitudinally.…”
Section: Considerations For Researchmentioning
confidence: 99%
“…However, if a continuous measure of relative weight is required, such as to assess change in adiposity, BMI z-scores and BMI-for-age percentiles will not be equivalent, and BMI-for-age percentiles are poorly suited for statistical analysis. 17 Analyses using BMI z-scores can be reported in BMI percentile units for interpretability, but BMI percentile should not be the analytic variable. BMI z-scores can be appropriately used to compare between group means and to model relative weight trajectories longitudinally.…”
Section: Considerations For Researchmentioning
confidence: 99%
“…Percentage BMI has been identified as an appropriate unit with which to measure adiposity change in children (Cole et al, 2005), but a review of the literature revealed no agreement as to the clinically significant level to aim for. For example, the SIGN guidelines suggest weight maintenance as an appropriate Childhood obesity treatment C Edwards et al outcome in most obese children (SIGN, 2003).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…A healthy weight in children and young adults is defined as a BMI at or below the 85 th percentile [54,67]. BMI-Z scores (BMI SD) are often computed to allow for comparison across age-and sex-specific BMI [8,23]. Compared with healthyweight peers, obese children have greater disability and worse quality of life [10,15,37,42,46].…”
Section: Introductionmentioning
confidence: 99%